Large intraperitoneal lipoma in pregnancy. (19th November 2014) - Mathen, Stephy; Nockolds, Claire; Arutchelvam, Satthiyabama
Abstract : Intraperitoneal lipomas causing high-grade bowel obstruction in advanced pregnancy are rare. We report an unusual case which presented at 33 weeks with faecal vomitus and abdominal pain. Lipomas are benign adipose tissue tumours that are usually asymptomatic. The constraints of diagnosis, investigation and treatment of such tumours in pregnancy are also discussed.